2014
DOI: 10.1016/j.math.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The deformation and longitudinal excursion of median nerve during digits movement and wrist extension

Abstract: The use of electronic devices, such as mobile phones and computers, has increased drastically among the young generation, but the potential health effects of carpal tunnel syndrome (CTS) on university students has not been comprehensively examined. Thirty-one university students aged 18 to 25 y with no symptoms of CTS were successfully recruited in this study. By using noninvasive ultrasonography, the morphological characteristics of the median nerve of each volunteer, and the extent of its longitudinal excurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The results of the present study can be explained 0.582 0.091 by the finding of Lai et al, who suggested that the median nerve became swollen after the students performed rapid mobile phone keying for 5min, indicated by a significant increase in the crosssectional area [14] .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results of the present study can be explained 0.582 0.091 by the finding of Lai et al, who suggested that the median nerve became swollen after the students performed rapid mobile phone keying for 5min, indicated by a significant increase in the crosssectional area [14] .…”
Section: Discussionsupporting
confidence: 63%
“…All participants were requested to sit on a chair facing the examiner with shoulder slightly abducted, the elbow of dominant hand flexed approximately at 90, forearm rested on the table in partially supinated (approximately 45º) to enable them to assume a posture generally applied when using a smartphone for text messaging. During the ultrasound examination, participants were instructed to move their thumb and keep other parts of the hand still when writing on smartphone [13,14] .…”
Section: Measurementsmentioning
confidence: 99%
“…Simoneau and Marklin (2001) recommended that typing with the keyboard at 5cm above elbow height is beneficial compared with placing the keyboard toward the user's lap, because wrist extension can be limited to 15° or less, which would theoretically reduce the risk of carpal tunnel syndrome. Compression of the median nerve at the wrist was also the least when wrist extension was below 15° (Lai et al, 2014).…”
Section: Work Surface Heightmentioning
confidence: 93%
“…Indeed, smartphone brings us many conveniences. However, increasing evidence shows that prolonged use of a smartphone, together with inappropriate wrist position, may lead to repetitive strain injury of the wrist, especially when fingers, hands and wrists are overused [ 1 ].…”
Section: Introductionmentioning
confidence: 99%